Study of the relationships of polymorphisms of the folate cycle genes with the levels of homocysteine and folic acid as risk factors of cardiovascular disorders in the post-covid period - A.A. Shuprovych; O.V. Zinych; N.M. Kushnareva; K.P. Komisarenko (Medičnì Perspektivi)
Enzymes of the folate cycle participate in the process of remethylation of homocysteine (HC) to methionine, where folates are coenzymes for methyl transfer. The aim of the work was to identify the interrelationships of gene polymorphisms of associations between folate cycle enzyme gene polymorphisms and cardiometabolic risk factors such as increased serum homocysteine levels and folic acid deficiency in patients in the post-covid period. In 51 patients who suffered from COVID-19, a general clinical and laboratory examination, and assessment of serum homocysteine and folic acid concentrations by immunoenzymatic method was carried out. Polymorphisms of the genes: methylenetetrahydrofolate reductase (677C>T and 1298A>C), methionine synthase-reductase (66A>G) and methionine synthase (2756A>G) were determined by real time polymerase chain reaction. For each of the named polymorphisms, the examined patients were divided into 3 groups according to the nucleotide alleles in the corresponding position: 1) homozygous dominant, 2) heterozygous and 3) homozygous recessive. For the methylenetetrahydrofolatereductase gene at position 677, serum levels of homocysteine and folate did not differ between the groups 1 and 2 with genotypes 677 C/C (n=26) and 677C/T (n=21), (p>0.05); in group 3, the recessive genotype 677 T/T was found in only 4 people (8%), that did not allow comparison of indices. The distribution of patients into 3 groups according to the genotype of the same gene at position 1298 revealed that the recessive 1298 C/C mutation in group 3 (n=9) associated with an increased homocysteine level (19.56±1.89 μmol/l), versus 10.68±0.76 (p=0.012) and 11.63±1.25 μmol/l (p=0.013) in groups 1 and 2, with no difference in folate levels between groups. Group 3 differed by a higher degree of obesity, a higher frequency of hypertension disease and chronic heart failure (in 85% of patients in group 3, against 41 and 50% in groups 1 and 2), a higher number of platelets, a longer duration of hospitalization due to COVID-19, a higher level of D-dimer. The study of groups of patients, divided depending on the genotype of methioninesynthase reductase at position 66, showed that carriers of the recessive homozygous 66 G/G mutation (group 3, n=15) had increased serum homocysteine level (16.56±1.64 μmol/l) in comparison with individuals of group 1 (n=17) 66 A/A (10.28±1.17 μmol/l; p=0.004) and group 2 (n=19) 66 A/G (11.32±1.17 μmol/l, p=0.013). In group 3, a longer duration of hospitalization due to COVID-19 was noted (17.15±1.65 vs. 11.88±0.97 days, p=0.008), higher frequency of hypertension (67% vs. 35%) and heart failure (67% against 29%) compared to group 1. The use of a molecular genetic approach made it possible to establish that the presence of recessive mutations of the folate cycle genes is associated with a potential predisposition to hyperhomocysteinemia, thrombophilia, severe forms of cardiometabolic complications and coronavirus disease.